2021
DOI: 10.1093/bjsw/bcab198
|View full text |Cite
|
Sign up to set email alerts
|

Mental well-being and quality of working life in UK social workers before and during the COVID-19 pandemic: A propensity score matching study

Abstract: During the COVID-19 pandemic interest into its potential impact on mental well-being has intensified. Within the social care sector, the pandemic has increased job demands and prolonged stress taking a disproportionate toll on the workforce, particularly social workers. This article compares the mental well-being and quality of working life of social workers in the United Kingdom (UK) before and during the pandemic. Data were collected in 2018 (N = 1,195) and 2020 (N = 1,024) using two cross-sectional surveys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Engaging in the negative, more avoidant coping strategies was also found in our earlier study phases [32][33][34] and within the literature, with the usage of these strategies being found to have a negative relationship and impact on mental wellbeing and resulting in increased burnout within the HSC workforce [50,60,62,63,[65][66][67]. Amongst respondents in Phase 3 of this present study there was widespread recognition that pandemic-related work responsibilities had affected respondents' quality of home life, with working from home not enabling a break from work for many of this workforce and it was noted that an emphasis should be placed on re/creating a more healthy work-life balance [68].…”
Section: Main Messages In Comparison With the Literaturesupporting
confidence: 82%
See 1 more Smart Citation
“…Engaging in the negative, more avoidant coping strategies was also found in our earlier study phases [32][33][34] and within the literature, with the usage of these strategies being found to have a negative relationship and impact on mental wellbeing and resulting in increased burnout within the HSC workforce [50,60,62,63,[65][66][67]. Amongst respondents in Phase 3 of this present study there was widespread recognition that pandemic-related work responsibilities had affected respondents' quality of home life, with working from home not enabling a break from work for many of this workforce and it was noted that an emphasis should be placed on re/creating a more healthy work-life balance [68].…”
Section: Main Messages In Comparison With the Literaturesupporting
confidence: 82%
“…The results of Phase 3 of this study will be used to expand on recommendations from earlier phases that could be used to inform policies and procedures for HSC employers to help counteract the adverse long-term effects the pandemic on mental wellbeing and work-related quality of life. Other papers linked to the wider study have explored the findings of the earlier phases [32,33], social care and social workers [34] and the 'clapping for carers' initiative [35].…”
Section: Introductionmentioning
confidence: 99%
“…This paper reports the findings of a study to examine the mental wellbeing, coping strategies, burnout and quality of working life of nurses, midwives and AHPs working throughout the UK at two separate time points during the COVID-19 pandemic (May–July 2020) and (November 2020–February 2021). Other papers have reported overall results [ 27 ] and findings specifically related to social care workers [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Direct comparison with results presented in this article is not possible because of different instruments used to measure PMH. Some studies, limited to specific population groups, such as social workers in McFadden et al or older adults in Hansen et al found mental well-being increased or remained stable relative to before pandemic (19,20). The maintained or improved level of PMH is attributed to population-specific factors that are not pervasive in the general population, and to the phase of the pandemic during which research took place, highlighting the accumulation and intensification of negative psychosocial experiences that results in deterioration of PMH in later stages of the pandemic (18,19).…”
Section: Discussionmentioning
confidence: 99%